2023
DOI: 10.1371/journal.pone.0284438
|View full text |Cite
|
Sign up to set email alerts
|

Buffering the effects of bad news: Exposure to others’ kindness alleviates the aversive effects of viewing others’ acts of immorality

Abstract: Negatively valenced news dominates the press, with stories of death and destruction gaining significant traction while also negatively impacting people’s mental health and perceptions of humanity. Given that horrific acts happen and need to be reported, we examined if news stories featuring others’ kindness could undo the aversive effects of news stories featuring others’ immorality. In Studies 1a-d we tested whether media exposure to the acts of kindness that occurred in response to a terrorist attack could a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…In a similar vein, recent studies relating to COVID-19 have shown that exposure to negative news about the pandemic triggered depression symptoms [ 30 ], increased self-reported mental distress [ 31 ], and was correlated with more severe self-reported mental health symptoms [ 32 ] and reductions in positive affect and optimism [ 33 ]. On the other hand, news stories featuring others’ kindness have been shown to have the potential to undo the aversive effects of negative news [ 34 ]. In the party context, which we study here, negative populist appeals have been shown to trigger negative emotions in their supporters [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, recent studies relating to COVID-19 have shown that exposure to negative news about the pandemic triggered depression symptoms [ 30 ], increased self-reported mental distress [ 31 ], and was correlated with more severe self-reported mental health symptoms [ 32 ] and reductions in positive affect and optimism [ 33 ]. On the other hand, news stories featuring others’ kindness have been shown to have the potential to undo the aversive effects of negative news [ 34 ]. In the party context, which we study here, negative populist appeals have been shown to trigger negative emotions in their supporters [ 35 ].…”
Section: Introductionmentioning
confidence: 99%